Application of sulfide-modified nanoscale zerovalent iron electrodes for electrokinetic remediation of chromium-contaminated soil in a three-dimensional electrode system. Issue 6 (December 2021) - He, Xiao; Cui, Guodong; Zhang, Qiming; Wang, Zheng; Tang, Tian; Liu, Yangsheng
Abstract: A modified electrokinetic remediation (EKR) system was designed to remediate Cr-contaminated soil using sulfidated nano-scale zerovalent iron (S-nZVI) as the third electrode. This study systematically compared the technological parameters and remediation efficiencies of three-dimensional (3D) electrokinetic systems using different materials as the third electrodes. The comparative experiment showed that the 3D EKR could effectively increase current efficiency, balance voltage distribution, alleviate excessive acidification or alkalization of soils and effectively improve the removal efficiency of Cr. Compared with other 3D electrodes, the S-nZVI electrode led to the higher currents and the more uniform voltage distribution; additionally, the leaching toxicities were reduced by 50.0–66.7%, and the removal efficiencies of total Cr (Cr(tot)) and hexavalent Cr (Cr(VI)) were increased by at least 15.4% and 22.6%, respectively. Cr(VI) was removed mainly resulting from the electrokinetic migration. Meanwhile, a small amount of Cr(Ⅵ) was converted to FeCr2 O4 and Cr 3+ OOH after reacting with S-nZVI in the middle region of the 3D EKR system. Due to the active layer of iron sulfides, S-nZVI was more stable and its electrokinetic efficiency was higher than other 3D electrodes, resulting in higher overall removal efficiencies. 3D EKR with S-nZVI can effectively decrease the toxicological effect of Cr contaminated soil at an experimental scale. The experimental findings from this study may provide a reference for guiding the development of more efficient methods for Cr-contaminated soil treatment. Graphical Abstract: ga1 Highlights: ● A three-dimensional electrokinetic system combining sulfide-modified nanoscale zerovalent iron electrodes was developed. ● S-nZVI showed better stability and electrical conductivity than other 3D electrodes. ● S-nZVI increased the removal efficiencies of total Cr and Cr(VI)) by at least 15.4% and 22.6%, respectively. ● Removal mechanisms of Cr(Ⅵ) in 3D EKR system with S-nZVI were electromigration, reduction and precipitation reactions.